Penggunaan Alkohol dan Sodium Hipoklorit sebagai Sterilan Tunggal untuk Sterilisasi Eksplan Kelapa Sawit - Dian Rahma Pratiwi; Sri Wening; Erwin Nazri; Yurna Yenni (Pusat Penelitian Kelapa Sawit, 2021)
Oil palm micropropagation through tissue culture is initiated with explants sterilization. Sterilization is a crucial stage because it determines the production rate of sterile plant cultures. Concentration and exposure time of sterilizing agents must be determined empirically to gain effective method which produces explants with low mortality. This research aimed to obtain effective protocols for unopened-leaves sterilization of oil palm using single sterilizing agents. Alcohol and sodium hypochlorite (NaOCl) at certain concentrations and duration of exposure were used as sterilization treatments. Treatments of alcohol did not show any significant differences on contamination, browning, and growth response rate based on analysis of variance (ANOVA) as well as sodium hypochlorite. The best results were shown by 70% alcohol for 5 minutes and 10% NaOCl for ten minutes. These treatments were sufficiently effective in reducing contamination with the lowest percentage of browning explants and high growth response rate. Application with higher concentration of alcohol (80% and 90%) caused death of explants, while higher concentration of sodium hypochlorite increased browning explants. The type of contamination found in culture were bacteria and fungi. Domination of bacteria was found in alcohol treatment while fungi contamination dominated in NaOCl treatment.